Experimental Production of Acute Arterial Thrombosis in the Carotid Artery of the Rat - Chan, K. E (Thrombosis and Haemostasis, 1967)
1. A simple but valid model for production of thrombosis in the rat carotid artery is described. The thrombi obtained resemble those obtained under natural circumstances.2. Disturbance of marginal blood flow in the artery appears to be the precipitating factor for thrombosis in the model.3. The use of this model for the assessment of antithrombotic agents is suggested.